The Black Man’s burden and the existentialist challenge: unchaining the African consciousness to action - Tom Eneji Ogar; Emmanuel Kelechi Iwuagwu (International Journal of Humanities and Innovation (IJHI), 2021)
This research work, “The Black Man’s Burden and the Existentialist Challenge: Unchaining the African consciousness to action,” is acritical analysis of the human condition in Africa that has remained intractable right from political independence to the present and the right approach to stem the tide towards the Africa of the future. How is it that none of the about forty-eight nations South of the Sahara have made appreciable and sustained progress since most achieved independence in the 1960s, except maybe a few with exceptional natural resources. It has been found out that what has become known as the Black Man’s burden is a consequence of unacceptable poverty rate, endemic corruption, civil strife, wars, terrorism, banditry, and a low level of human growth and development. The idea that Western countries of Europe and America hold the key to Africa’s development is a myth that is not worth patronizing. The answer to the Black Man’s burden lies as they should in the hands of African countries themselves and especially the individuals and their governments. It is not the case that Africa has been the only continent in history that has suffered this human condition. Europe in the aftermath of the world wars was in shambles, and it took some conscious efforts of individuals and governments to consciously revolt against the absurd through a commitment to come out of the vicious cycle of finger-pointing as causes. The Black Man’s burden can also be addressed using the existentialist movement as a theoretical framework to bring Africa out of the present malaise of backwardness. An acceptance of the absurd and a conscious revolt against the same is what we need in Africa to address this sisyphusian like scenario.